Factors Influencing Survival Status of HIV/AIDS after HAART in Huzhou City, Eastern China - Meihua Jin; Zhongrong Yang; Jing Li; Xiaoqi Liu; Zhenqian Wu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Highly active antiretroviral therapy (HAART) can effectively reduce the risk of death and opportunistic infections in patients with HIV/AIDS. The aim of this study was to analyse the survival status and its influencing factors in HIV/AIDS after HAART. Methods. The data on patients’ sociodemographic characteristics, treatment information, and follow-up results from the Information Management System of the Chinese Center for Disease Control and Prevention were obtained. Bivariate and stepwise multivariate Cox proportional hazards regression model analyses were performed. Results. A total of 1812 participants were included in this study, of which 1716 were still alive (survival group) and 96 had died (death group). The results indicated that respondents who were elderly (HR = 1.053, 95% CI: 1.037–1.069, P<0.01), who had heterosexual transmission (HR = 2.422, 95% CI: 1.314–4.465, P<0.01) and whose current WHO clinical stage was stage III or IV (HR = 2.399, 95% CI: 1.215–4.735, P<0.05) were more likely to have died; respondents whose baseline CD4+ T-lymphocyte count was equal to or more than 200 cells/μL (HR = 0.412, 95% CI: 0.275–0.616, P<0.05) were unlikely to have died. Conclusions. It is recommended that HAART be provided to HIV/AIDS patients at an early clinical stage and that the health services for HIV/AIDS patients after taking medicines be strengthened, which will help promote adherence to therapeutic regimens and improve quality of life.